Ocorrência do linguado-zebra, Gymnachirus nudus Kaup, 1858 (Pleuronectiformes: Achiridae) no litoral do Estado de São Paulo e aspectos morfométricos do otólito - Nucci, Maria Gabriela [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
O linguado-zebra, Gymnachirus nudus, é um peixe de fundo pertencente à família Achiridae, capturado regularmente pela frota de parelha no litoral do Estado de São Paulo e rejeitado a bordo, pois não tem valor econômico. No presente estudo foram analisados 116 exemplares com comprimentos totais entre 90 e 190 mm, sendo 46 machos, 63 fêmeas e sete indeterminados. A relação comprimento peso foi exponencial (a=1,7425; b=0,224; r2=0,8654) e a relação entre otólito e comprimento total resultou na equação da reta (a=0,1404; b=0,0201; r2=0,7058) Os otólitos sagitta de 46 exemplares foram extraídos e medidos caracterizando-se como de perfil retangular, arredondado na parte superior e irregular com duas saliências na parte inferior.

The naked sole, Gymnachirus nudus, is a bottom-dwelling fish belonging to the Achiridae family, regularly captured by the pair trawl fishing fleet along the coast of the State of São Paulo and rejected on board, once has no economic value. In the present study, 116 specimens with total lengths between 90 and 190 mm were analyzed, 46 males, 63 females and seven indetermined. The length-weight relationship was exponencial (a=1,7425; b=0,224; r2=0,8654), and the relation between otolith and total length resulted in the linear equation (a=0,1404; b=0,0201; r2=0,7058). The sagitta otoliths of 46 specimens were extracted, measured and characterized as having a rectangular profile, rounded at the top and irregular with two projections at the bottom.
Occurrence of the naked sole, Gymnachirus nudus Kaup, 1858 (Pleuronectiformes: Achiridae) on the coast of the State of São Paulo and morphometric aspects of the otolith
Keywords: Ictiologia; Linguado (Peixe); Otólito; Morfometria